PROSES PEMBENIHAN DAN AKLIMATISASI MIKROORGANISME DARI LIMBAH PABRIK PERMEN UNTUK LUMPUR AKTIF - titiresmi, Titiresmi (BPPT)
To process wastes biologically beside knowing quality of wastes a seeding process and a microbial acclimatization are needed in order to develop microbes capable of degrading organic compounds in the wastes. Samples were taken from aeration tank of PT. Van Melle Indonesia, a candy factory, which were then poured into separated tank to be batch-aerated for 4 months. Such a microbial seeding plays an important role in aerobically waste treatments. Beside COD,VSS values being a seeding-threshold measure (more than 3000 mg/l) for being used in an aerobe process. During 1 month seeding the VSS concentration was high, i.e. approximately 6000 mg/l. However, the effi ciency of COD removal was not appropriate because of high organic loads. Thus, nutrient-less treatments were run for 2 weeks seeding (day-57 to day-75). During theperiod VSS concentrations decreased from 6000 mg/l to 4000 mg/l. After nutrients additions on day-78 VSS start to increase along with the increasing of COD values. During day-94 to day-118 period, the achieved effi ciency of COD removal was more than 80% although the VSS values were low. At day-124 VSS concentration was 3122 mg/l and COD removal effi ciency was 91%.After the seeding process was stabilized then an acclimatization step, i.e. a process to adapt microorganisms to wastewater being treated, was performed. This process was carried out in a batch type digester. Adapting process was run by substituting glucose with wastewater being treated. The fi nal process was COD removal effi ciency of more than 80%.Key words : Microorganisms, aerobe, aeration, VSS, COD.